Investigating simplified modeling choices for numerical simulation of CO2 storage with thermal effects. (May 2018) - Andersen, Odd; Nilsen, Halvor M.
Abstract: Temperature is a key variable for the modeling of geological CO2 storage, and any simulation model must take it explicitly or implicitly into account. At the large spatial scales and low flow rates associated with CO2 migration studies, temperature can be reasonably considered as an constant and imposed external field, with CO2 and brine assumed to be in thermal equilibrium with the surrounding rock. Closer to an injection well, the picture is different. CO2 may be injected at a temperature significantly different from that of the aquifer, leading to an expanding thermal front around the injection well. The local change in temperature not only affects fluid properties, but also geomechanical stresses and the rate of geochemical reactions. In this article, we examine whether certain simplified approaches used to simulate CO2 storage at the large scale may be adapted and applied to model the regions affected by the thermal front. We do this by comparing the results from upscaled (vertically integrated) flow models extended with heat transport and different choices of overburden representations against highly resolved 3D models. The considered test cases have been constructed to minimize or maximize specific characteristics of the coupled flow-thermal system: the Peclet number, the gravity number and the amount of thermal bleed. Our results suggest that for several practical cases the thermal front can be reasonably well modeled using a vertically integrated flow model with constant vertical temperature. The results also suggest that a simplified overburden representation may give a reasonable approximation, particularly for scenarios with low thermal bleed. We point out that the impact of a simplified overburden representation can be very similar to the use of linear heat transfer coefficients. On the other hand, while models that completely neglect thermal bleed may perform acceptably in some low-bleed settings, they often lead to very large errors.